AI-based interactive digital game development in social studies learning to enhance students’ computational thinking - Anggraini, Diana Noor; Kokom Komalasari; Sopianingsih, Pitria; Insani, Nisrina Nurul; Sudrajat, Fajar Agustian (Jurnal Inovasi Teknologi Pendidikan, 2025)
Students’ computational thinking skills in higher education remain relatively low, particularly in learning contexts that require problem decomposition, abstraction, and systematic problem solving. This condition highlights the need for innovative learning approaches that actively engage students through digital technology. This study aims to develop an Artificial Intelligence (AI)-based interactive digital game project in Social Studies learning to enhance students’ computational thinking skills. The study employed a Research and Development (R&D) design involving a preliminary study, conceptual model development, validation, revision, and implementation. The research population consisted of undergraduate students enrolled in Social Studies Education courses at an Indonesian university, from whom 60 were selected using purposive sampling based on their participation in project-based learning activities. Data were collected through questionnaires, observations, and field notes. Qualitative data were analysed using interactive analysis techniques, while quantitative data were examined using Pearson correlation and simple linear regression. The findings reveal that student involvement in AI-based interactive digital game development projects positively influences computational thinking skills, including decomposition, pattern recognition, abstraction, and algorithmic thinking. These results indicate that integrating AI into project-based learning effectively supports the development of essential 21st-century skills.